ANALISIS HAMBATAN GURU DALAM PEMANFAATAN INTERACTIVE FLAT PANEL (IFP) PADA MATA PELAJARAN MATEMATIKA DI SDN CIRACAS 14 JAKARTA TIMUR - Hasbullah; Timorwoko, Agus; Dewi Insyirah, Annisa; Puspitasari, Eka; Novita, Ira; Haikal Hafizo Akbari, Muhammad; Nurlaeli; Magfirah, Nurul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the obstacles faced by teachers in utilizing Interactive Flat Panel (IFP) in mathematics learning at SDN Ciracas 14 East Jakarta and to identify recommendations for optimizing its use. The research employed a qualitative descriptive approach involving classroom teachers as the main subjects. Data were collected through observations, in-depth interviews, and documentation, then analyzed using data reduction, data display, and conclusion drawing techniques. The findings indicate that IFP has a positive impact on mathematics learning by increasing students’ motivation, engagement, and participation through interactive visual, audio, and multimedia features. However, its utilization has not yet reached its optimal function as an interactive learning medium. Most teachers still use IFP primarily for presentations and video displays rather than maximizing advanced interactive features. The main technical obstacles include unstable internet connections, unresponsive touchscreens, connectivity issues, and limited availability of IFP units. Meanwhile, non-technical obstacles include the lack of comprehensive training, limited teacher competence in advanced IFP features, restricted access to interactive mathematics applications, and dependence on external learning resources. The study concludes that the successful implementation of IFP depends not only on the availability of technology but also on teacher readiness, continuous professional development, adequate infrastructure, and institutional support for educational digitalization.